Assessment of Agricultural Residue to Produce Activated Carbon-Supported Nickel Catalysts and Hydrogen Rich Gas. - Hosseinzaei, Behnam; Hadianfard, Mohammad Jafar; Esmaeilzadeh, Feridun; Recio-Ruiz, María del Carmen; Ruiz-Rosas, Ramiro Rafael; Rosas-Martínez, Juana María; Rodríguez-Mirasol, José; Cordero-Alcántara, Tomás (MDPI, 2023)
The aim of this study was to synthesize chemically activated carbons from different agricultural residues, i.e., pistachio shell (PS), bitter orange peel (OP), and saffron petal (SP), and subsequently to use them as supports for loading a Ni catalyst. Supercritical water gasification of bio-oil was applied to investigate the catalytic performance of the resulting catalysts. The physicochemical properties of the activated carbon (ACs) and the catalysts (Ni/ACs) were characterized with BET, XRD, XPS, TEM, and TPD. The adsorption results showed that the ACs developed considerable pore structures, containing both micro- and mesopores, which was validated by the well-distributed active phases on the supports in the TEM images. Furthermore, it was found that the BET of AC(PS) was 1410 m2/g, which was higher than that of AC(OP) (1085 m2/g) and AC(SP) (900 m2/g). The results obtained from XRD mainly indicated the presence of the nickel phosphides phases, which was confirmed with the XPS and TPD analyses. The catalytic tests showed that by raising the process temperature, the total amount of gas and hydrogen increased. Furthermore, Ni/AC(PS) showed a superior catalytic activity. The highest total gas amount (i.e., 7.87 mmol/g bio-oil), together with 37.2 vol.% H2, was achieved using Ni/AC(PS) with a 1:10:100 catalyst:bio-oil weight ratio and a mass ratio of 1:10 (bio-oil/water) at T = 550 °C.
Keywords: Carbón activado; Níquel; Hidrógeno; Residuos agrícolas; Activated carbon; Agricultural residue; Mesoporosity; Nickel phosphide; Supercritical water; Hydrogen